Workload profiles prior to injury in professional soccer players. Issue 3 (2nd September 2017) - Lu, Donna; Howle, Kieran; Waterson, Adam; Duncan, Craig; Duffield, Rob
ABSTRACT: This study examined if a particular profile of internal and external workload existed prior to injury. Forty-five professional soccer players were monitored over two seasons. For each non-contact injury, a profile of workload variables was determined for 4 weeks and expressed as (i) an absolute, (ii) week-to-week change and (iii) relative to the player's season mean. Variables included exposure, session rating of perceived exertion (s-RPE) workload, total distance, low-, high-, very-high-speed running distance, mean speed, bodyload, monotony and strain. Acute:chronic workload ratio was also calculated and sensitivity of the relative workload was tested. Absolute and relative exposure and s-RPE workload were greater in all 3 weeks compared to the injury week ( P  < 0.05). However, no significant differences were evident between the 3 weeks prior to injury for all variables ( P  > 0.05). Acute:chronic workload ratio for s-RPE was significantly greater than acute:chronic workload ratio for very-high-speed running ( P  = 0.04). A workload threshold of 114% of a player's season mean reported low sensitivity and specificity for exposure (25.6[20.2–33.5]% and 73.9[22.6–28.2]%, ) and s-RPE workload (16.3[12.6–24.9]% and 79.9[20.3–26.1]%, respectively). No specific load profile existed, although high-sustained exposure and s-RPE were evident for the 3 weeks prior to injury. Consequently, load prescription should be aware of sustained high workloads.